Deep evolution of carbonated magmas controls ocean island basalt chemistry - Junlong Yang; Chao Wang; Zhenmin Jin; Zhicheng Jing (Nature Communications)
Abstract The composition of ocean island basalts (OIBs) is key to understanding mantle differentiation and quantifying intra-plate carbon outflux. Existing petrogenesis models fail to simultaneously reproduce the low SiO2 and low SiO2/FeOT characteristics of alkalic OIBs and ignore melt-orthopyroxene reactions in the lithosphere that may further elevate the SiO2 content of primary magmas. Here we show experimentally that high-degree (>50%) high-pressure crystallization of carbonated primary magmas at the base of lithosphere drastically reduces both the SiO2 content and SiO2/FeOT ratio, due to the combined effects of clinopyroxene and garnet precipitation and carbonates dissolution. The major-element chemistry of alkalic OIBs can be quantitatively reproduced by considering varying degrees of crystallization, melt-orthopyroxene reactions, and source CO2 content. Our results imply high intra-plate carbon outfluxes and support the observed association of low OIB SiO2 contents with low mantle potential temperatures, as slower magma transport at lower temperatures leads to more extensive crystallization and reaction.